2009
DOI: 10.1128/jb.00530-09
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol Utilization Is Required for Regrowth of In Vitro Hypoxic Nonreplicating Mycobacterium bovis Bacillus Calmette-Guerin

Abstract: Mycobacteria store triacylglycerols (TGs) under various stress conditions, such as hypoxia, exposure to nitric oxide, and acidic environments. These stress conditions are known to induce nonreplicating persistence in mycobacteria. The importance of TG accumulation and utilization during regrowth is not clearly understood. Here we specifically determined the levels of accumulated TG and TG lipase activity in Mycobacterium bovis bacillus Calmette-Guerin (BCG) in various different physiological states (logarithmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 28 publications
7
127
0
Order By: Relevance
“…The sum compositions indicated that the smaller TGs were probably esterifi ed with C16, C18, and C19 FAs, whereas longer C22, C24, and C26 acyl functions probably esterifi ed the larger, stationary phase-specifi c TGs. The latter observation fi ts well with previous structural reports of mycobacterial TG ( 13,32,33 ). To further support this structural information, the most-abundant logarithmic and stationary phase TG group [M+NH 4 ] + ions were targeted for collisioninduced dissociation MS/MS ( Fig.…”
Section: Assessment Of Mtb Lipid Profi Les From Different Growth Phasessupporting
confidence: 60%
“…The sum compositions indicated that the smaller TGs were probably esterifi ed with C16, C18, and C19 FAs, whereas longer C22, C24, and C26 acyl functions probably esterifi ed the larger, stationary phase-specifi c TGs. The latter observation fi ts well with previous structural reports of mycobacterial TG ( 13,32,33 ). To further support this structural information, the most-abundant logarithmic and stationary phase TG group [M+NH 4 ] + ions were targeted for collisioninduced dissociation MS/MS ( Fig.…”
Section: Assessment Of Mtb Lipid Profi Les From Different Growth Phasessupporting
confidence: 60%
“…We have previously shown that THL inhibits growth of M. bovis BCG and re-growth of bacilli from hypoxic NRP (11). This is also the case for the THL analog used here (supplemental Fig.…”
Section: Esterase (Protein) Levels and (Enzymatic) Activity Correlatementioning
confidence: 49%
“…See also accumulation of large amounts of TAG was quantitatively a most prominent change in lipid composition on entry into nonreplicating conditions, and these TAG deposits were hydrolyzed during regrowth (supplemental Fig. S3A, S3B) (11). In addition, total cellular esterase activity, assessed by esterlinked fluorescent dye (FITC conjugated CMFDA, supplemental Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous components of the DosR regulon of M. smegmatis are also DosR dependent in pathogenic mycobacteria, including multiple universal stress proteins (30,31), a ribosome stabilizingfactor (32,33), and putative energy metabolism genes (e.g., diacylglycerol acyltransferases, nitroreductases) (34,35) (Tables S1 and S2). The DosR regulon of M. smegmatis also controls the expression of some genes that are not DosR dependent or are absent from the pathogen (Table S2), most notably 10 genes involved in hydrogen metabolism and 6 genes linked to sulfur metabolism ( Fig.…”
Section: Transcription Of Two [Nife]-hydrogenases Depends On Dosrmentioning
confidence: 99%